Ichthyosis prematurity syndrome: clinical evaluation of 17 families with a rare disorder of lipid metabolism - Khnykin, Denis; Rønnevig, Jørgen; Haußer-Siller, Ingrid (Journal of the American Academy of Dermatology, 2012)
Background Ichthyosis prematurity syndrome (IPS) is classified as a syndromic congenital ichthyosis based on the presence of skin changes at birth, ultrastructural abnormalities in the epidermis, and extracutaneous manifestations. Recently, mutations in the fatty acid transporter protein 4 gene have been identified in patients with IPS. Objective We sought to perform a detailed clinical evaluation of patients with IPS identified in Norway. Methods Clinical examination and follow-up of all patients (n = 23) and light and electron microscopic examination of skin biopsy specimens were performed. Results IPS was characterized prenatally by ultrasound findings of polyhydramnios, separation of membranes, echogenic amniotic fluid, and clear chorionic fluid. All patients were born prematurely with sometimes life-threatening neonatal asphyxia; this was likely caused by aspiration of corneocyte-containing amniotic fluid as postmortem examination of lung tissue in two patients revealed keratin debris filling the bronchial tree and alveoli. The skin appeared erythrodermic, swollen, and covered by a greasy, thick vernix caseosa-like “scale” at birth, and evolved rapidly to a mild chronic ichthyosis. Many patients subsequently had chronic, severe pruritus. Histopathologic and ultrastructural examination of skin biopsy specimens showed hyperkeratosis, acanthosis, dermal inflammation, and characteristic aggregates of curved lamellar structures in the upper epidermis. Peripheral blood eosinophilia was invariably present and most patients had increased serum immunoglobulin E levels. Over 70% of the patients had a history of respiratory allergy and/or food allergy. Limitations The study included only 23 patients because of the rarity of the disease. Conclusion IPS is characterized by defined genetic mutations, typical ultrastructural skin abnormalities, and distinct prenatal and postnatal clinical features.
Published online August 22, 2011
Gesehen am 16.08.2018